Histology-based survival outcomes in hormone receptor-positive metastatic breast cancer treated with targeted therapies - Jason A. Mouabbi; Akshara Singareeka Raghavendra; Roland L. Bassett; Amy Hassan; Debu Tripathy; Rachel M. Layman (npj Breast Cancer, 2022)
Abstract The addition of targeted therapies (TT) to endocrine therapy (ET) has improved the outcomes of patients with HR-positive, HER2-negative metastatic breast cancer (mBC). However, it is unknown whether patients with invasive lobular carcinoma (ILC) or mixed invasive ductal and lobular carcinoma (mixed) histologies experience the same magnitude of benefit from this therapy as those with invasive ductal carcinoma (IDC). We aim to determine whether patients with IDC, ILC, and mixed HR+/HER2− mBC derive similar benefit from the addition of cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6is), mammalian target of rapamycin inhibitor (mTORi), and phosphoinositide 3-kinase inhibitor (PI3Ki) to ET in HR+/HER2− mBC. We conducted an observational, population-based investigation using data from the MD Anderson prospectively collected database. We conducted a histology-based analysis of progression-free survival (PFS) and overall survival (OS) durations in 3784 patients with HR+/HER2− mBC who were treated with TT plus ET between January 1, 2010, and December 31, 2021. Out of the 3784 patients, 2975 were included in the final analysis. Of these, 2249 received CDK4/6is (81% IDC, 15% ILC, and 4% mixed), 1027 received everolimus (82% IDC, 14% ILC, and 4% mixed) and 49 received alpelisib (81% IDC and 19% ILC). The addition of targeted therapy to ET did not result in statistically significant differences in PFS or OS duration among patients with IDC, ILC, and mixed HR+/HER2− mBC. We concluded that for patients with HR+/HER2− mBC, the addition of TT to ET leads to a similar magnitude of benefit, irrespective of histology.